2010
DOI: 10.1002/cncr.25274
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin for the treatment of pain syndrome related to radiation‐induced mucositis in patients with head and neck cancer treated with concurrent chemoradiotherapy

Abstract: BACKGROUND: This retrospective study evaluated the efficacy of gabapentin for the treatment of pain syndromes related to radiation-induced mucositis in patients with head and neck cancers treated with concurrent chemoradiation. METHODS: Data from 42 patients with head and neck malignancies treated with concurrent chemoradiotherapy using an intensity-modulated radiotherapy technique were analyzed. Gabapentin was initiated in the second week of radiotherapy. Opiates were prescribed in addition to gabapentin as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 24 publications
1
64
0
Order By: Relevance
“…The efficacy of gabapentin was assessed by examining the need for opioids for pain relief. The authors concluded that gabapentin can provide pain relief and reduce the need for opioids [5,6]. No guideline was possible due to insufficient evidence.…”
Section: Gabapentinmentioning
confidence: 99%
“…The efficacy of gabapentin was assessed by examining the need for opioids for pain relief. The authors concluded that gabapentin can provide pain relief and reduce the need for opioids [5,6]. No guideline was possible due to insufficient evidence.…”
Section: Gabapentinmentioning
confidence: 99%
“…Pretreatment assessment of dental status and treatment of preexisting dental and gingival disease can prevent osteonecrosis. In patients with pain syndrome related to radiation‐induced oral mucositis in cases of concomitant chemotherapy, gabapentin has been shown to significantly reduce oral pain …”
Section: Recommendationsmentioning
confidence: 99%
“…This mucositis may be aggravated by preexisting dental and gingival disease and may make eating and swallowing very difficult. Although pain medicine will likely be necessary, topical and/or systemic treatments that may be necessary include antibacterial and antifungal medications or gabapentin . Primary care clinicians should be aware that oral antibiotics for unrelated, systemic infections increase the likelihood of fungal overgrowth and infection in the oral cavity.…”
Section: Recommendationsmentioning
confidence: 99%
“…A review of cancer trials found that adjuvant analgesics added to opioids provide additional relief, usually within 4 to 8 days, with the strongest evidence for gabapentin 138. Another report described the successful use of gabapentin to reduce mucositis pain in patients receiving concomitant radiotherapy and chemotherapy 139…”
Section: Pharmacologic Treatments For Cancer Painmentioning
confidence: 99%